AGING EFFECT ON SALIVARY GLAND : A REVIEW - Ongko, Felix Hartanto; How, Kim-Chuan; Halim, Susanna (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Swallowing disorders and dry mouth are the most common oral conditions faced by aging adults. Dry mouth increases the risk of dental caries, periodontal disease, candidiasis, oral ulceration, dysphagia which can have a negative impact on nutritional status and quality of life. Saliva secreted in oral cavity is essential for food ingestion and plays an important role in sensory perception. Aging affects salivary glands and changes quantity and quality of saliva. Alterations in salivary gland function can have adverse effects on oral and systemic health. Salivary hypofunction is associated with decreased chewing and swallowing ability as well as objective taste perception. Many medical conditions and drug treatments usually affect saliva through anticholinergic activity in older adults. Lifestyle factors will also modify saliva gradually over time. Besides histological gland atrophy, physiological effects of aging cause changes in salivary gland function due to decreased intensity of stimulation and reflexes in elderly population. With increasing age, there is a reduction in the number of olfactory and taste receptors, decreased neuronal salivary stimulation and decreased blood perfusion at the gland level. Complex relationship between aging and salivary changes have variability results in elderly subjects and still need many research to point out the main problem. ABSTRAKGangguan menelandan mulut kering merupakan kondisi mulut yang palingumumdialamioleh orang dewasa yang menua. Mulut kering meningkatkan risikokaries gigi, penyakit periodontal, kandidiasis, ulserasi oral, disfagia yang dapat berdampak negatif pada status gizi dan kualitas hidup. Air liur yang disekresikan dalam rongga mulut sangat pentinguntuk menelan makanan dan berperan penting dalam persepsi sensorik. Penuaan memengaruhi kelenjar ludah dan mengubah kuantitas dan kualitas air liur. Perubahan fungsi kelenjar ludah dapat berdampak buruk pada kesehatan mulut dan sistemik. Hipofungsi saliva dikaitkan dengan penurunan kemampuan mengunyah dan menelan serta persepsi rasa objektif. Banyak kondisi medis dan perawatan obat biasanya memengaruhi air liur melalui aktivitas antikolinergik pada orang dewasa yang lebih tua. Faktor gaya hidup juga akan mengubah air liur secara bertahap seiring berjalannya waktu. Selain atrofi kelenjar histologis, efek fisiologis penuaan menyebabkan perubahan fungsi kelenjar ludah karena penurunan intensitas rangsangan dan refleks pada populasi lanjutusia. Dengan bertambahnyausia, terjadi penurunan jumlahreseptor penciuman dan pengecap, penurunan rangsangan sarafterhadap air liur, dan penurunan perfusi darah di tingkat kelenjar. Hubungan yang kompleks antara penuaan dan perubahan saliva memiliki hasil yang bervariasi pada subjek lanjut usia dan masih memerlukan banyak penelitian untuk menunjukkan masalah utamanya.